THE BODY IN PLATO: AN INVESTIGATION BASED ON PHAEDO AND PHAEDRUS (Fiep Bulletin - online, 2013)
Plato is appointed as the founder of a well structured thought that divides and contrasts the body and soul, which mark the comprehension in a predominant occidental way of thinking about those elements. That is why it is so important to discuss the body's conception and its characteristics in the thought of one of the most influential philosophers of the world to discuss the epistemological foundation of the Physical Education. Therefore, this research has the objective of reflecting about the body's conception in Plato. The methodology used in this work is bibliographic. Some Plato's dialogues were studied, mainly Timaeus, Phaedo and Phaedrus and some commentators who approach general themes or specifics themes about the soul and the body were also considered. Initially, general platonic's theory will be studied. In the next topic, the man's nature is the central theme. At last, the death conception and the implication of the disconnection of the body will be explored. As in platonic's world theory, the man is understood in a dual way. A part is eternal and it is connected with the divine: the soul. The other is always changing and it is corruptible: the body. Thereby, the philosopher should try to release from the body the most and go beyond the purely terrain dimension.
Keywords: Plato; body; dual human nature